2020
DOI: 10.1038/s43018-020-0036-4
|View full text |Cite|
|
Sign up to set email alerts
|

Long-distance modulation of bystander tumor cells by CD8+ T-cell-secreted IFN-γ

Abstract: T-cell-secreted interferon (IFN)-γ can exert pleiotropic effects on tumor cells that include induction of immune checkpoints and antigen presentation machinery components, and inhibition of cell growth. Despite its role as a key effector molecule, little is known about the spatiotemporal spreading of IFN-γ secreted by activated CD8 + T cells within the tumor environment. Using multiday intravital imaging, we demonstrate that T cell recognition of a minor fraction of tumor cells leads to sensing of IFN-γ by a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 49 publications
13
96
1
2
Order By: Relevance
“…In our data CTL apoptosis increased over time, so we introduced a resistance variable R to account for this. This is consistent with recent reports that long range IFN-γ signalling can cause upregulation of PD-L1 in cells across distances of up to 800 [26] ; or that IFN-γ-dependent invasion of m μ myeloid-derived suppressor cells could be the major source of suppression [27] ; or other immune checkpoint death receptors such as FAS-L [28] ; or perhaps competition between tumour cells and CTLs for nutrients was a primary mediator of CTL apoptosis in our model, since both activated CTLs and tumour cells rely heavily on anaerobic glycolysis or glycolysis as sources of fuel [29] , and interactions between CTLs and stromal cells resulted in catastrophic destruction of tumour vasculature [30] , which ought to result in a reduction in glucose supply to the tumour and might account for increased apoptosis of CTLs over time. It would be useful to acquire more experimental data which could shed light on the reasons for this apparent time-increasing apoptosis rate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our data CTL apoptosis increased over time, so we introduced a resistance variable R to account for this. This is consistent with recent reports that long range IFN-γ signalling can cause upregulation of PD-L1 in cells across distances of up to 800 [26] ; or that IFN-γ-dependent invasion of m μ myeloid-derived suppressor cells could be the major source of suppression [27] ; or other immune checkpoint death receptors such as FAS-L [28] ; or perhaps competition between tumour cells and CTLs for nutrients was a primary mediator of CTL apoptosis in our model, since both activated CTLs and tumour cells rely heavily on anaerobic glycolysis or glycolysis as sources of fuel [29] , and interactions between CTLs and stromal cells resulted in catastrophic destruction of tumour vasculature [30] , which ought to result in a reduction in glucose supply to the tumour and might account for increased apoptosis of CTLs over time. It would be useful to acquire more experimental data which could shed light on the reasons for this apparent time-increasing apoptosis rate.…”
Section: Discussionsupporting
confidence: 93%
“…Invading CTLs have 2 different T effects on tumour cells: either killing which occurs at rate (CTL -1 day -1 ), or induction of k e the quiescent state which happens at rate (CTL -1 day -1 ). Our quiescent state is k q motivated by observations of an -dependent cell-cycle arrest in B16F10 melanoma F N γ I after ACT [20] , which we previously implicated in control of murine EL4 lymphoma [6] and for which there is also evidence in ovarian and breast carcinoma models [26] . In B16F10 melanoma, quiescent tumour cells recover from CTL induced cell cycle arrest after a few days [20] .…”
Section: Effects Of Ctls On Tumoursmentioning
confidence: 99%
“…IFNGR-interferon gamma receptor; IDILs-interferon-driven inhibitory ligands; TILs-tumor infiltrating lymphocytes; ISGs-interferon signature genes; ICB-immune checkpoint blockade; TME-tumor microenvironment Thibaut et al recently suggested a model in which tumor-reactive T-cells secrete IFN-γ, which diffuses extensively to alter the TME in distant areas. The prolonged activity of IFN-γ has been shown to be crucial for antitumor immune response [107] as shown by induction of PD-L1 expression and inhibition of tumor growth [108]. Furthermore, Zhang et al proposed that IFN-γ may be a good therapeutic option for improving the efficacy of PD-1 blockade therapy for pancreatic cancer by preventing the trafficking of CXCR2+ CD68+ immunosuppressive macrophages to the TME by blocking the CXCL8-CXCR2 axis [109].…”
Section: Ifn-γ Contributes To the Efficiency Of Cancer Immunotherapymentioning
confidence: 99%
“…Interactions with several targets may provide signal integration and facilitate amplification of the immune response or target cell elimination. Furthermore, polarized secretion could still induce signal spreading as the immunological synapse does not spatially restrict IFNγ secretion by CTLs, allowing IFNγ bystander activity important to alter tumor environment (Sanderson et al, 2012;Hoekstra et al, 2020;Thibaut et al, 2020).…”
Section: Cytokine Secretionmentioning
confidence: 99%